Kecemasan Terhadap Berita Hoax pada Millennial Mom - Rizki Putri Ayudini (CV. Syntax Corporation Indonesia, 2022)
This study aims to describe anxiety toward hoax news at millennial mom. The research method used is quantitative descriptive. The data collection technique used the instrument developed by Spielberger (1983) State Trait Anxiety Inventory (STAI) Form Y-1 with 24 samples. Data analysis method used is descriptive statistic using Rasch Model. The results of this study illustrate most of samples (i.e 58%) had low score of anxiety and the others (i.e 42%) had high score of anxiety. The anxiety also illustrate based on the status of marriage, education status, number of children, education level of children, employment status, number of active social media accounts, age of social media, and duration in daily usage of social media